2013
DOI: 10.1007/s00383-013-3274-z
|View full text |Cite
|
Sign up to set email alerts
|

Amyand’s hernias in childhood (a report on 21 patients): a single-centre experience

Abstract: Although a routine appendectomy is not required for a normal-looking appendix, in a case where the inflammatory status of the appendix adheres to the surface of the hernia sac, an appendectomy is required. We believe that USG examination in the diagnosis of Amyand's hernias can provide additional contribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 15 publications
0
28
0
1
Order By: Relevance
“…Regarding the treatment of Amyand’s hernias, many authors suggest that prophylactic appendectomy is not necessary when the appendix is found without signs of inflammation [18,19]. By contrast, other authors suggest that all patients have an appendectomy because the appendix could reherniate or, especially in younger patients, cause appendicitis [20].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the treatment of Amyand’s hernias, many authors suggest that prophylactic appendectomy is not necessary when the appendix is found without signs of inflammation [18,19]. By contrast, other authors suggest that all patients have an appendectomy because the appendix could reherniate or, especially in younger patients, cause appendicitis [20].…”
Section: Discussionmentioning
confidence: 99%
“…When the appendicitis is found in Amyand's hernia, the performance of an appendectomy is virtually wise. However, some authors are reluctant when the appendix shows no signs of inflammation, while others suggest the realization of prophylactic appendectomy, citing the possibility of recurrence of hernia and the difficulty of later diagnosis of complications [3235]. Findings on autopsy of Amyand's hernia in victims who have succumbed to other diseases show that this can remain asymptomatic throughout life [10].…”
Section: Discussionmentioning
confidence: 99%
“…Amyand's hernia occurs in 1% (0.19-1.7%) of all inguinal hernia cases (2,3,6,11). In 0.13% of all cases, the appendix is inflamed.…”
Section: Pathophysiologymentioning
confidence: 99%
“…(4) Inflammatory swelling of the appendix may be the beginning of a vicious cycle. Thus, Amyand's hernia becomes irreducible, accentuating the swelling due to venous stasis and causing an impaired microcirculation of the appendix wall, resulting in bacterial overgrowth and translocation (11,12).…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation